Development of a Volleyball Physical Education Learning Model Based on Social Emotional Learning to Improve Vocational High School Students’ Learning Outcomes - Wahyudin; setya rahayu (Journal of Physical Education and Sports, 2026)
Research on the development of a volleyball PJOK learning model based on Social Emotional Learning (SEL) for Vocational High School students. The study used the Research and Development (R&D) method, following the Borg and Gall model, including the stages of needs analysis, product development, expert validation, and small- and large-scale trials. The research subjects consisted of 3 PJOK teachers and 90 students from 3 vocational high schools in Indramayu Regency. Data were collected through observation, questionnaires, and learning outcome tests, and analysed using descriptive statistics, paired-samples t-tests, N-Gain, and effect sizes. The results of the needs analysis showed an initial completeness level of only 40%. The results of expert validation showed a very feasible category with a percentage of 83.00%–85.00%. Teacher responses were in the very practical category (83.33%–85.00%), while student responses were in the practical category, with an average of 75.28% in small-scale trials and 74.28% in large-scale trials. The effectiveness test results showed an increase in learning outcomes, with N-Gain values of 0.46 (medium) and 0.70 (high), and effect sizes of 0.70 and 2.95. Thus, the SEL-based volleyball PJOK learning model was declared feasible, practical, and effective.